IMPLEMENTASI APLIKASI QUIZIZZ SEBAGAI MEDIA EVALUASI ONLINE PADA PEMBELAJARAN TEKS PIDATO PERSUASIF KELAS IX SMPN 10 MALANG - Paramadhika, Dinda Aldita Salsabillah (Hasta Wiyata, 2023)
The emergence of several problems in learning persuasive speech materials creates its own challenges for teachers, especially when Distance Learning (PJJ) takes place. Distance Learning (PJJ) has been in place since the coronavirus spread in Indonesia, precisely in March 2020. This research was conducted when PJJ took place at SMPN 10 Malang with the research subjects of all 9H grade students numbering 30 students. The purpose of this study is to find out the results of the implementation of the Quizizz application on persuasive speech text learning. The approach used in this study is the quantitative approach. Research data is obtained from the process of conducting tests, spreading questionnaires, conducting observations, and interviews. The collected data is then processed by doing various calculations including the calculation of the validity of the problem item, the reliability of the problem, the different power of the problem, the difficulty level of the problem, and also the percentage calculation of the spread of the questionnaire. The SPSS application was also used in the study to measure the accuracy of the data. The results of this study revealed that (1) positive responses from students while learning using Quizizz, (2) Quizizz applications can increase student learning interest, (3) increase student achievement outcomes. Based on the results of the spread of questionnaires that state that 70% of students agree or are happy when learning to use the Quizizz application.Overall, the results explained that ninth graders felt more excited and experienced increased grades when using the Quizizz application during PJJ.